A Practical Strain Sensor Based on Ecoflex/Overlapping Graphene/Ecoflex Sandwich Structures for Vocal Fold Vibration and Body Motion Monitoring - Fan, Yanyan; Zhao, Hongbin; Yang, Yifan; Yang, Yi; Ren, Tianling; Tu, Hailing (Frontiers in Sensors, 2022)
Graphene-based stretchable and flexible strain sensors are one of the promising “bridges” to the biomedical realm. However, enhancing graphene-based wearable strain sensors to meet the demand of high sensitivity, broad sensing range, and recoverable structure deformation simultaneously is still a great challenge. In this work, through structural design, we fabricated a simple Ecoflex/Overlapping Graphene/Ecoflex (EOGE) strain sensor by encapsulating a graphene sensing element on polymer Ecoflex substrates using a drop-casting method. The EOGE strain sensor can detect stretching with high sensitivity, a maximum gauge factor of 715 with a wide strain range up to 57%, and adequate reliability and stability over 1,000 cycles for stretching. Moreover, the EOGE strain sensor shows recoverable structure deformation, and the sensor has a steady response in the frequency disturbance test. The good property of the strain sensor is attributed to the resistance variation induced by the overlap and crack structure of graphene by structural design. The vibrations caused by sound and various body movements have been thoroughly detected, which exhibited that the EOGE strain sensor is a promising candidate for wearable biomedical electronic applications.